Mucosal pathobiology and molecular signature of epithelial barrier dysfunction in the small intestine in irritable bowel syndrome - González‐Castro, Ana M.; Martinez, Cristina (Journal of gastroenterology and hepatology research, 2017)
Irritable bowel syndrome (IBS) is one of the most prevalent gastrointestinal disorders in developed countries. Its etiology remains unknown; however, a common finding, regardless of IBS subtype, is the presence of altered intestinal barrier. In fact, signaling and location of cell-to-cell adhesion proteins, in connection with increased immune activity, seem abnormal in the intestinal epithelium of IBS patients. Despite that most research is performed on distal segments of the intestine, altered permeability has been reported in both, the small and the large bowel of all IBS subtypes. The small intestine carries out digestion and nutrient absorption and is also the site where the majority of immune responses to luminal antigens takes place. In fact, the upper intestine is more exposed to environmental antigens than the colon and is also a site of symptom generation. Recent studies have revealed small intestinal structural alterations of the epithelial barrier and mucosal immune activation in association with intestinal dysfunction, suggesting the commitment of the intestine as a whole in the pathogenesis of IBS. This review summarizes the most recent findings on mucosal barrier alterations and its relationship to symptoms arising from the small intestine in IBS, including epithelial structural abnormalities, mucosal immune activation, and microbial dysbiosis, further supporting the hypothesis of an organic origin of IBS.